Analisis Pengaruh Direktur dan Komisaris Wanita terhadap Performa Perusahaan Asuransi Jiwa di Indonesia - Kandrasyah, Arya; Denita, Graciala; Ambar, Dyah; Fresno, Musa; Hanggraeni, Dewi (E-Jurnal Akuntansi, 2019)
This research aims to determine whether the composition and attributes of female in the company’s board influence the performance of life insurance companies in Indonesia. The method used in this research is quantitative method, with pooled least square multiple regression technique. This research sample consist of 22 life insurance company in Indonesia on the 2014-2018 period. This research result shows that the female composition on the company’s board influences the performance of life insurance companies in Indonesia. While the educational and multi-directorship attributes, as well as corporate governance affect the performance of life insurance companies in Indonesia . Keywords : Performance; Female director; Female commissioner; Corporate Governance; Life Insurance.